Library Services and Social Capital for Sustainable Development Initiatives in Nigeria: The Moderating Role of Collective Action - Augustine Uzoma Madu; Zaharudin Ibrahim; Norhayati Hussin (Record and Library Journal, 2026)
Background of the study: Alliance between library services and social capital is undeniable in sustainability studies, especially sustainable development initiatives as an emerging concept. Purpose: This study investigated the relationship among, social capital, and sustainable development initiative, moderated by users’ likelihood to engage in collective actions. Method: A descriptive correlational research design was adopted. A systematic simple random sampling was used to select 439 private university and public library users in Northern Nigeria. Data was collected through Google form distributed via the WhatsApp link. Findings: Results revealed that LSs had a significant relationship with SC at β=.752, t=22.54, p<0.05, SC also had a significant relationship with SDIs at β=0.607, t=13.32, p<0.05. Further results showed that there was a significant relationship between LSs and SDIs with β=0.456, t=9.56, p<0.05, while likelihood to engage in collective action significantly moderate the relationship between social capital and sustainable development initiatives with β=0.109, t=3.069, p<0.05. Conclusion: Beyond information systems status; libraries are social change agents which offer services that boost social capital to enhance sustainable development ideals.